MENINGGALKAN JALAN TEROR: - Gazi Saloom (Jurnal Dialog, 2014)
There has been a long debate among multi-discplinary experts on terrorism regarding how to fight against terrorism. Most experts agreed that terrorism could not be eliminated by military forces as military approach could trigger the emergence of terrorists’ self recycle character. Some psychologists (such as Garfinkel, 2007; John Horgan, 2009; Noricks, 2009; Choudhury, 2009; Nauman, 2010) are of the opinion that deradicalization and disengagement can be used to prevent and encounter terrorism. This paper throws some light upon theories of deradicalization and disengagement proposed by some leading experts based on literature reviews. Additionally, it also identifies strength and weakness of each approach.